INFORMATION TECHNOLOGY AND ROMANIAN HIGHER EDUCATION - EVIDENCE ON LINKED DYNAMIC - Nichifor, Bogdan (Studies and Scientific Researches. Economics Edition, 2014)
The link between education, in general, and information technologies is one that does not necessarily have to be demonstrated. But it is interesting to see the specific link that is established between these two components of modern society. In recent years, part-time education forms tend to occupy an increasingly important position in the Romanian higher education from the perspective of the total number of students opting for distance learning or traditional part-time learning. This development occurred amid expansion of information technology - more and more households have Internet access and frequency of its use is increasing from year to year – in the context in which forms of part – time learning require the use of this means of information and communication. On this background more and more people over 25 years become interested in further developing their studies, including employed persons opting for further studies, increasing the share of students over 25 years in total students and the share of employed population over 25 years with higher education in total in respective age group.